2023
DOI: 10.1002/oby.23792
|View full text |Cite
|
Sign up to set email alerts
|

Food reinforcement architecture: A framework for impulsive and compulsive overeating and food abuse

Abstract: Few reward‐based theories address key drivers of susceptibility to food cues and consumption beyond fullness. Decision‐making and habit formation are governed by reinforcement‐based learning processes that, when overstimulated, can drive unregulated hedonically motivated overeating. Here, a model food reinforcement architecture is proposed that uses fundamental concepts in reinforcement and decision‐making to identify maladaptive eating habits that can lead to obesity. This model is unique in that it identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 137 publications
0
3
0
Order By: Relevance
“…Through cue-reward reinforcement learning processes, this may establish attentional biases toward ultraprocessed foods. It has been posited that propensity for this type of food cue–reward learning contributes to impulsive eating (ie, frequent food cue–potentiated consumption) and thus increases risk for excess weight gain . This risk for weight gain may be amplified by additional aberrant eating patterns (eg, delayed satiation) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through cue-reward reinforcement learning processes, this may establish attentional biases toward ultraprocessed foods. It has been posited that propensity for this type of food cue–reward learning contributes to impulsive eating (ie, frequent food cue–potentiated consumption) and thus increases risk for excess weight gain . This risk for weight gain may be amplified by additional aberrant eating patterns (eg, delayed satiation) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been posited that propensity for this type of food cue–reward learning contributes to impulsive eating (ie, frequent food cue–potentiated consumption) and thus increases risk for excess weight gain . This risk for weight gain may be amplified by additional aberrant eating patterns (eg, delayed satiation) . Limitations include the cross-sectional nature of the study and self-reported measures of the home food environment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a concept related to eating behaviour known as food reinforcement explores how much effort an individual is willing to exert to obtain tasty food [ 4 ]. Research indicates that there are individual differences, with obese individuals showing a greater incidence of food addiction and greater attachment to food than non-obese individuals [ 5 ].…”
Section: Introductionmentioning
confidence: 99%